KEBIJAKAN PENDIDIKAN PADA PERGURUAN TINGGI ISLAM: TRANFORMASI STAIN DAN IAIN MENJADI UIN - Husain, Saddam; Dwi Wahyuni, Andi Eki (Jurnal Pendidikan Kreatif, 2023)
STAIN/IAIN as Islamic educational institutions are required to meet the needs of the community who want general education within the scope of Islamic education. If the STAIN/IAIN cannot respond, then this institution will be used as a second choice by the community and may even be abandoned by the community. The idea of ​​transforming IAIN/STAIN into UIN was based on many factors, including the desire to carry out scientific integration so as to create a complete university, meet market needs and as a response to the emergence of modernization and globalization.